2017
DOI: 10.1021/acsami.7b07941
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced X-Band Electromagnetic-Interference Shielding Performance of Layer-Structured Fabric-Supported Polyaniline/Cobalt–Nickel Coatings

Abstract: Despite tremendous efforts, fabrication of lightweight conductive fabrics for high-performance X-band electromagnetic-interference (EMI) shielding remains a daunting technical challenge. We herein report an ingenious and efficient strategy to deposit polyaniline/cobalt-nickel (PANI/Co-Ni) coatings onto lyocell fabrics that involves consecutive steps of in situ polymerization and electroless plating. The PANI-Co-Ni ternary-component system successfully induced a synergistic effect from EM wave-absorption and EM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(79 citation statements)
references
References 41 publications
1
78
0
Order By: Relevance
“…This stable composite film with a thickness of 10-15 µm displayed good shielding effectiveness of 30-35 dB with mechanical strength of 179 MPa. Zhao et al [421] synthesized a layer-structured shielding composite prepared by the successive coating of PANI and magnetic alloy cobalt-nickel which showed relatively high SE of 34-46 dB. Similar work was also achieved on layered linen fabric/PPy/nickel (LF/PPy/Ni) composites.…”
Section: Electromagnetic Interference Shieldingmentioning
confidence: 89%
“…This stable composite film with a thickness of 10-15 µm displayed good shielding effectiveness of 30-35 dB with mechanical strength of 179 MPa. Zhao et al [421] synthesized a layer-structured shielding composite prepared by the successive coating of PANI and magnetic alloy cobalt-nickel which showed relatively high SE of 34-46 dB. Similar work was also achieved on layered linen fabric/PPy/nickel (LF/PPy/Ni) composites.…”
Section: Electromagnetic Interference Shieldingmentioning
confidence: 89%
“…Zhao et al [61] and Gschwind et al [38] both proposed the use of organic conductive polymers as the cathode. In one paper, polyaniline (PANI) was used in combination with a chlorideconducting polymer electrolyte.…”
Section: Cathode Developmentmentioning
confidence: 99%
“…They were also skeptical as to the "reduction" would work independently or whether chloride or some other species might be involved. [62][63][64][65] A completely different cathode material was proposed by Zhao et al, [61] who coated a carbon nanotube substrate with chloride-ion-doped polypyrrole (PPy) by means of a chemical oxidative polymerization procedure to yield a chloride-iondoped PPy cathode. A maximum capacity of 118 mA h g -1 was achieved.…”
Section: Cathode Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Zhao et al reported the fabrication of layered structure with lyocell fabrics, PANI and cobalt–nickel (Co–Ni) by electroless plating approach. The PANI/Co–Ni composites coated lyocell fabric exhibited high EMI SE of 46.22 dB in the X band region when compared to their single counterparts (PANI‐coated fabric and Co–Ni‐coated fabric) . The three phase heterostuctures of F‐NiFe2O4/PANI coated on Polyimide fabrics by layer by layer structure coating for EMI shielding applications was designed by wang et al .…”
Section: Emi Shielding Of Conductive Polymer Coated Fabricsmentioning
confidence: 99%